The Ethics of Ethnographic Attraction: Reflections on the Production of the Finno-Ugric Exhibitions at the Estonian National Museum - Svetlana Karm; Art Leete (Journal of Ethnology and Folkloristics)
We intend to explore the production of the Finno-Ugric exhibitions at the Estonian National Museum. Our particular aim is to reveal methodological changes of ethnographic reproduction and to contextualise the museum’s current efforts in ideologically positioning of the permanent exhibition. Through historical–hermeneutical analysis we plan to establish particular museological trends at the Estonian National Museum that have led curators to the current ideological position. The history of the Finno-Ugric displays at the Estonian National Museum and comparative analysis of international museological practices enable us to reveal and interpret different approaches to ethnographic reconstructions. When exhibiting indigenous cultures, one needs to balance ethnographic charisma with the ethics of display. In order to employ the approach of ethical attraction, curators must comprehend indigenous cultural logic while building up ethnographic representations.